Penggunaan Alat Pelindung Diri dan Keracunan Pestisida pada Pekerja di Perusahaan Penyemprot Hama - Gurdani Yogisutanti; Ivanna Ajeng Mulianti; Indah Nurmalina; Linda Hotmaida; Suhat Suhat (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
The pest control service industry is one of the industries in the field of pest control services, especially those in residential areas that use pesticides that can be harmful, especially for pest sprayers. The purpose of this study was to determine the use of Personal Protective Equipment (PPE) with pesticide poisoning in workers in pest spraying companies. This study used a cross-sectional design with a sample of 30 people spraying pests at PT Zeta Prima Lestari with a total sampling method. Univariate, bivariate analysis, and statistical tests use coefficient contingency. Measurement of serum cholinesterase levels was carried out at Borromeus Hospital Bandung. The results showed the characteristics of the respondents most respondents aged 21-30 years (63.3%), working period of more than 1 year were 43.3%, smoking habits (70.0%), the duration of exposure were mostly more than 5 hours per day (90%), there were still those who did not use PPE in full (3.3%) and the BMI of respondents in thin and fat conditions was 26.7%. Statistical test results showed that the variable use of PPE is associated with serum cholinesterase levels (p = 0.0001), but age (p = 0.573), years of service (p = 0.245), smoking habits (p = 0.506), length of exposure (p = 0.735), BMI (p = 0.540) and Hb levels (p = 0.690) are not related. Based on research results that pest sprayers who use PPE in full will be better protected from exposure to pesticides. The recommended recommendation is to monitor the use of PPE before work and periodic serum cholinesterase checks on pest sprayers.